2017
DOI: 10.1039/c6tb03223k
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan–poly(caprolactone) nanofibers for skin repair

Abstract: Dermal wounds, both acute and chronic, represent a significant clinical challenge and therefore the development of novel biomaterial-based skin substitutes to promote skin repair is essential. Nanofibers have garnered attention as materials to promote skin regeneration due to the similarities in morphology and dimensionality between nanofibers and native extracellular matrix proteins, which are critical in guiding cutaneous wound healing. Electrospun chitosan-poly(caprolactone) (CPCL) nanofiber scaffolds, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 76 publications
(68 reference statements)
0
55
0
Order By: Relevance
“…Nowadays other skin substitutes made of synthetic polymers, such as PLGA, polycaprolactone, or polypyrrole, are being investigated to generate membranes as platforms to seed fibroblasts …”
Section: Cellular Substitutesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays other skin substitutes made of synthetic polymers, such as PLGA, polycaprolactone, or polypyrrole, are being investigated to generate membranes as platforms to seed fibroblasts …”
Section: Cellular Substitutesmentioning
confidence: 99%
“…33 Nowadays other skin substitutes made of synthetic polymers, such as PLGA, polycaprolactone, or polypyrrole, are being investigated to generate membranes as platforms to seed fibroblasts. [37][38][39][40][41][42] Regarding composite allografts, Apligraf â is a bovine collagen-based substitute which is more complex than previous substitutes since it includes fibroblasts and keratinocytes. It is often used for the treatment of diabetic foot ulcers, accelerating wound healing.…”
Section: Cellular Substitutesmentioning
confidence: 99%
“…The nanofiber-based mats have shown great potential as scaffolds for applications in tissue engineering. [12][13][14] In our prior studies, we have demonstrated the fabrication of scaffolds with both uniaxially aligned and random nanofibers in adjacent regions to recapitulate the structural organization of collagen fibrils at the tendon-to-bone insertion. [8][9][10][11] On the other hand, random nanofibers are better suited for the repair of disorganized tissues such as bone, skin, and cartilage.…”
Section: Doi: 101002/marc201900579mentioning
confidence: 99%
“…This blending of CS with synthetic polymers facilitates the tailoring of the degradation rates required for specific applications . Among commercially available synthetic polymers, polycaprolactone (PCL) is used widely for biomedical applications . PCL is a biocompatible and biodegradable polyester.…”
Section: Introductionmentioning
confidence: 99%
“…18 Among commercially available synthetic polymers, polycaprolactone (PCL) is used widely for biomedical applications. 36 PCL is a biocompatible and biodegradable polyester. It is a hydrophobic polymer and has very good solubility in organic solvents and blending compatibility with a variety of polymers.…”
Section: Introductionmentioning
confidence: 99%